Envejecimiento y delirium: un viejo conocido en el Departamento de Urgencias (2014)
With increasing life expectancy, it is coming to a marked increase of the geriatric diseases in emergency departments; multifactorial disease and increasingly of interest in the clinical setting. example of this reality is the delirium, which in the past 30 years has produced a marked interest in the medical literature as a result of the Renaissance as a diagnosis in the emergency units and intensive care, probably as a result of the emergence of medical specialties as geriatrics who have rescued the old man’s disease, this article presents a review of delirium in emergency departments and their correlation with the aging population.